Effect of temperature on bacterial community in petroleum hydrocarbon-contaminated and uncontaminated Antarctic soil - Chong, Chun Wie; Silvaraj, Santha; Supramaniam, Yasoga; Snape, Ian; Tan, Irene Kit Ping (Springer Verlag, 2018)
It is generally accepted that bacterial diversity in a community confers resistance to environmental perturbation. Communities with high bacterial diversity are less likely to be impacted by environmental changes such as warming. As such, hydrocarbon-contaminated Antarctic soil that are typically characterised by low bacterial diversity and highly selective taxonomic composition are expected to be more sensitive to changes in temperature than uncontaminated Antarctic soil. To test this hypothesis, we evaluated the response of bacterial community structure to warming of hydrocarbon-contaminated and uncontaminated soil collected from Casey Station, Windmill Island, East Antarctica by using microcosms incubated at 5, 10 and 15 °C over a period of 12 weeks. Our results showed that shifts occurred in the bacterial community in relation to the incubation temperatures in both the hydrocarbon-contaminated and uncontaminated soil, with a stronger response observed in the contaminated soil. Taxa referred as comprising hydrocarbon-degrading genera such as Rhodococcus, was the most prevalent genus in the contaminated soil after incubation at 15 °C, accounting for approximately 32–50% of the total detected genera. However, there were no significant differences in the selected functional genes, potentially suggesting high levels of metabolic plasticity in the studied soil bacterial communities. Overall, we showed that hydrocarbon contamination in soil might lead to lower bacterial community stability against environmental perturbation such as temperature variation.